Industrial solid waste recycling using digital servitisation for decarbonisation to promote Net zero in the circular economy - Gao, Pengqun; Zhou, Yang; Sun, Lipeng; Alahmari, Saad; Innab, Nisreen; Venkatachalam, K.; Ferrara, Massimiliano (Computers & industrial engineering, 2025)
•Research integrates AI, blockchain, and data analytics for efficient stakeholder coordination in recycling.•The project has 3 phases: Returned product clustering, Requirement Elicitation, and Smart Life Cycle Selection.•IFC-MCA optimises product allocation to centres based on category, return time, price, and location.•LDA identifies consumer needs, analyses return patterns, predicts volumes, enhancing resource use.•MCNN recommends product life cycle options based on quality and life expectancy, enhancing sustainability. The smart circular economy framework proposed in this study encourages a net-zero economy by improving industrial solid waste recycling for decarbonization through the digital service economy. A blockchain-based cloud platform uses advanced technologies like artificial intelligence, blockchain, and data analytics to encourage smooth communication between all parties. These suggested framework developments include requirement elicitation and quality grading, smart life cycle option selection, and returned products clustering. The FuzClu algorithm clusters returned products to improve their allocation to collection centers based on specific features like product type, return time and location. Subsequently, requirement elicitation through Latent Dirichlet Analysis identifies consumer needs and return patterns to produce innovation and predict future return volumes. Finally, the Smart Life Cycle Option Selection applies the Modified Convolutional Neural Network Algorithm to recommend optimal life cycle options based on product quality and lifetime. This approach increases the value of end-of-life products, encourages sustainability and reduces environmental pollution. Overall, this research contributes to addressing industrial solid waste challenges by aligning digital servitisation with circular economy principles, notably supporting decarbonisation with a focus on a net-zero economy.